Identifikasi Morfometrik Belangkas (Family: Limulidae) Di Pantai Tanjung Punai Kabupaten Bangka Barat - Fuad, Akmal Nur; Aisyah, Siti; Pratiwi, Fika Dewi; Roanisca, Occa; Swandi, Monica K. (Journal of Tropical Marine Science, 2024)
Tanjung Punai is one of the beach in the coastal area of ​​West Bangka Regency which has conditions in the form of sandy beaches and mangrove ecosystems. These conditions support various biota that live and develop, one of which is the horseshoe crab. Horseshoe crab are aquatic invertebrates belonging to the phylum Arthropoda and the family Limulidae. The morphometric characters of horseshoe crab doves have different variations based on geographical area. This research aims to identify horseshoe crab based on morphology and morphometrics in Tanjung Punai Beach. The research was carried out in April-May 2022 at Tanjung Punai Beach, West Bangka Regency. The research method uses methods purposive sampling as well as data analysis using Independent Samples T-Test and simple linear regression analysis. The species found is Carcinoscorpius rotundicauda and Tachypleus gigas. The significance value is 0.00 (p < 0.05) and the t value thit > ttab shows that there are differences in the average morphometric characters between the two species.